The cost of providing and scaling up surgery: a comparison of a district hospital and a referral hospital in Zambia. Issue Volume 33:Issue10(2018) (6th November 2018) - Bijlmakers, Leon; Cornelissen, Dennis; Cheelo, Mweene; Nthele, Mzaza; Kachimba, John; Broekhuizen, Henk; Gajewski, Jakub; Brugha, Ruairí
Abstract: The lack of access to quality-assured surgery in rural parts of sub-Saharan Africa, where the numbers of trained health workers are often insufficient, presents challenges for national governments. The case for investing in scaling up surgical systems in low-resource settings is 3-fold: the potential beneficial impact on a large proportion of the global burden of disease; better access for rural populations who have the greatest unmet need; and the economic case. The economic losses from untreated surgical conditions far exceed any expenditure that would be required to scale up surgical care. We identified the resources used in delivering surgery at a rural district-level hospital and an urban based referral hospital in Zambia and calculated their cost through a combination of bottom-up costing and step-down accounting. Surgery performed at the referral hospital is ∼50% more expensive compared with the district hospital, mostly because of the higher cost of hospital stay. The low bed occupancy rates at the two hospitals suggest underutilization of the capacity, and/or missing elements of needed capacity, to conduct surgery. Nevertheless, our study confirms that scaling up district-level surgery makes sense, through bringing economies of scale, while acknowledging the need for more comprehensive assessments and costing of capacity constraints. We quantified the economies of scale under different scaling scenarios. If surgery at the district hospital was scaled up by 10, 20 or 50%, the total cost of surgery would increase proportionately less than that, i.e. by 6, 12 and 30%, respectively. If this were to lead to less demand for surgery at the referral hospital, say 10% less surgery, it would result in a reduction of 2.7% in the total cost. Although the health system as a whole would benefit, the referring hospitals would not derive the full economic benefit, unless Government increased resources for district-level surgery.